2012
DOI: 10.1108/09513541211251406
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge strategies for enhancing school learning capacity

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 32 publications
3
23
0
Order By: Relevance
“…These findings support the assertions of previous studies such as those of Leung [42] and Cheng [43], who both indicated that promoting KS practice within an educational environment helps members of staff to discuss different ideas about teaching methods, experiences, and skills that could increase the effectiveness of teaching and learning performance, thus supporting process innovation. The findings are also congruent with Ferraresi et al [44], who argued that KM processes, namely capturing, sharing, and application, can enhance innovation through the strategic orientation of the organisation.…”
Section: Discussionsupporting
confidence: 81%
“…These findings support the assertions of previous studies such as those of Leung [42] and Cheng [43], who both indicated that promoting KS practice within an educational environment helps members of staff to discuss different ideas about teaching methods, experiences, and skills that could increase the effectiveness of teaching and learning performance, thus supporting process innovation. The findings are also congruent with Ferraresi et al [44], who argued that KM processes, namely capturing, sharing, and application, can enhance innovation through the strategic orientation of the organisation.…”
Section: Discussionsupporting
confidence: 81%
“…Product innovation is enhanced when organisational members exchange information, insights, skills, lessons learned, and experiences [17]. The knowledge-based view suggests that organisations need to generate as well as share knowledge [13], [27]. When knowledge is used, learning takes place which in turn leads to changes of behaviour and innovation [2], [28].…”
Section: Resultsmentioning
confidence: 99%
“…These studies have examined how the intensification of change forces within the school system (e.g., Y. C. Cheng & Walker, 2008) has reshaped the role of school leaders as well as their priorities and daily practice (Y. C. Cheng & Mok, 2007;Kwan, 2011;Lam, 2004;Walker & Ko, 2011). In concert with this focus on organizational change, research has also explored the role of leadership in developing organizational capacity (e.g., Bain, Walker, & Chan, 2011;E. Cheng, 2012;Y.…”
Section: Topical Distributionmentioning
confidence: 98%